A Bridge Not Too Far: Reflections on the Politico-Economic Thought of Kym Thorne. Issue 2 (2nd April 2016) - Dahlstrom, Timothy R.
Abstract : In the assessment and critique of ontology and epistemology, few have ventured into the often esoteric realm of economics. One of those few brave souls is Kym Thorne. The focus of his critique is centered on the policies and perspectives of neoliberal expression in economics, as well as its corollaries in public administration. His critical perspective provides a bridge from practice to theory. However, that bridge is not as long as it might have been. Thorne's analysis provides only an entry into an even deeper critique of neoliberal monetarism, as well as its competing perspectives. This reflection will assess, with brevity, Thorne's contribution to economic thought, describe its limitations, and extend the bridge.